4PL in Supply Chain Management (SCM) System - Mishra, Sanjeev Kumar (Prabandhan: Indian Journal of Management, 2010)
Today, Globalization has made the trading of products and services very relevant to the world. It has revolutionized the world over last few decades. The company can fulfill the needs of its customers very effectively by the help of the new technologies being innovated in the field of merchandising. By the help of contrived flow of information, physical distribution and money, the delivery of the products and services can be performed from the raw materials to the end customers. Supply chain comprises of the network of facility and arrangement options- from the procurement of raw materials to transformation into final products and ultimately distribution of these finished products to the end customer. The regulation of this network can be achievable because of Supply Chain Management (SCM). It encompasses the movement of goods to and from the partner organizations holistically. The integration of demand and supply management can be made possible through SCM.